Um percurso entre o oral e o escrito em redações escolares de séries finais do Ensino Fundamental II e do Ensino Médio - Morais, Vanessa Pelissari de Marchi (2023)
This dissertation linked to the line of research Text and discourse on oral and written modalities, from the Post-Graduation Studies Program on the Portuguese Language at Pontifícia Universidade Católica de São Paulo, aims to identify and analyze the orality marks within the organization of dissertative texts produced by elementary school students at the regular age. The general goal of our investigation is to develop a study about how the orality register occurs in the organization of dissertative texts produced by students at the 6th and 9th grades of Elementary School II and at the third grade of High School. Regarding the specific goals, we aim: I) To establish the relation between the anchoring and the formulated opinion; II) Identify how the concept formation occurs in the studied school essays; III) Point to how the development of topics in the analyzed essays happens; IV) Report the use of engagement marks between peers; the use of opinion marks and conversational marks. From the methodologic perspective, this research is descriptive, qualitative approach and of interpretative foundation. The theoretical contribution that bases the research is constituted by the following authors: Koch e Fávero (1987); Travaglia (1991, 2002, 2009); Siqueira (1995); Fávero, Andrade e Aquino (1999); Fávero (1999); Marcuschi (2002, 2010); Galembeck (2008 e 2009); Jubran (2019). The corpus is constituted by fifteen essays produced by students at the 6th and 9th grades of Elementary School II and the third grade of High School from a private school at the municipality of Tremembé-SP, collected at the year of 2021. We have observed that the orality marks were present in all texts, as expected for students at the analyzed school stage. We have seen that such marks could weaken the argumentation presented in the texts. However, we have noticed that, as there is a cognitive growth from the apprentice, the orality marks appear in a smaller quantity or a less expressive one. Therefore, the bigger the student’s cognitive growth, the bigger is their commitment about the act of writing